Estimation of the Spatial Coordinates of Air Objects in Synchronous Radar Networks for Airspace Observation - Svyd, I.; Obod, I.; Maltsev, O.; Vorgul, O.; Chumak, V.; Bakumenko, B. (PIC S&T, 2021)
In the presented work, a study was made of the influence of errors in assessing the location of receiving points of a multi-position radar system, as well as mismatch of time scales of points for receiving signals of a multi-position radar system, due to the finite stability of time generators in the considered synchronous information radar network for observing airspace, on the accuracy of assessing the location of observed air objects. This showed the possibility of implementing synchronous radar networks for observing the airspace on the basis of the existing fleet of primary and secondary radars.
Keywords: multi-position radar system; air object; data processing; airspace control systems; air traffic control